Neutron Capture Cross Section for 10Be. (October 2020) - Volknandt, M; Eberhardt, K; Endres, A; Erbacher, P; Fix, M; Göbel, K; Heftrich, T; Heinitz, S; Hrivula, E; Junghans, A; Käppeler, F; Kivel, N; et al.
Abstract: The determination of the involved reaction cross sections is essential for the understanding of how the big bang nucleosynthesis and nuclear reactions in stars contribute to the observed abundances. One of those, which has not been measured so far, is the 10 Be(n, γ) cross section. A 10 BeO sample, provided by PSI Villigen, was irradiated in a cyclic activation at the TRIGA reactor in Mainz. The characteristic γ-rays following the decay of 11 Be were measured using LaBr3 scintillation detectors. The thermal neutron cross section and the resonance integral were experimentally determined for the first time.